1999
DOI: 10.1038/eye.1999.54
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of phacotrabeculectomy using 10-0 polyglactin sutures

Abstract: These mid-term results show that 10-0 Vicryl compares favourably with other suture materials the results of which have been reported, and obviates the need for routine use of antimetabolites or for post-operative manipulations at the slit-lamp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…However, light ocular massage was required in 12.5% of their patients in the immediate postoperative period. 8 In our retrospective study, we could not determine the accurate number of patients who required ocular massage. However, despite the use of polygalactin sutures, 16 (11.5%) eyes needed argon laser suturelysis of the nylon suture at the end of 3 months.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…However, light ocular massage was required in 12.5% of their patients in the immediate postoperative period. 8 In our retrospective study, we could not determine the accurate number of patients who required ocular massage. However, despite the use of polygalactin sutures, 16 (11.5%) eyes needed argon laser suturelysis of the nylon suture at the end of 3 months.…”
Section: Discussionmentioning
confidence: 98%
“…One can further argue that the method of using the polyglactin suture for scleral flap closure can be used for wound modulation after glaucoma surgery in the early postoperative period. Vyas et al 8 have reported the benefits of 10-0 polyglactin use in phacotrabeculectomy using a 5-mm scleral tunnel and single-piece polymethyl methacrylate (PMMA) intraocular lens without antimetabolite in a prospective study. They found that the use of polyglactin eliminated the need for the routine use of antimetabolites or for postoperative manipulations at the slit lamp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The V10-0 sutures seemed particularly appropriate to treat non-penetrating corneal lacerations in zone 1 (OTC group) in first-line therapy, for mutually non-exclusive reasons: 1) The properties of the polyglactin 910 has shown advantages since the seventies [ 19 ]: mainly in pediatric cataract surgery [ 6 ] avoiding suture removal, and more marginally in adults cataract surgery [ 9 ], or in combined glaucoma surgery [ 20 , 21 , 22 ] reducing the risk of early over-filtration and preserving filtering bleb without additional inflammation. Its characteristics have only been studied on simple linear surgical incisions and never to our knowledge in mechanical corneal wounds.…”
Section: Discussionmentioning
confidence: 99%